2024
DOI: 10.1039/d3lc00729d
|View full text |Cite
|
Sign up to set email alerts
|

Development and future of droplet microfluidics

Lang Nan,
Huidan Zhang,
David A. Weitz
et al.

Abstract: This review introduces the development of droplet microfluidics by explaining the physical mechanisms of droplet generation, discussing various approaches in manipulating droplets, and summarizing key applications in material science and biological analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 201 publications
0
13
0
Order By: Relevance
“…1,2 In these applications, it is crucial to have precise control over droplet characteristics, including shape, size, and generation frequency. 3 Numerous studies have demonstrated that the flow rate ratio of the two phases, the viscosity ratio, and the channel structure are the key parameters for regulating the characteristics of Newtonian droplets with simple rheological behavior. [4][5][6] Nevertheless, the mechanisms that affect the characteristics of droplets with complex rheological properties in microchannels are still relatively unknown.…”
Section: Role Of Elasticity On Polymeric Droplet Generation and Morph...mentioning
confidence: 99%
“…1,2 In these applications, it is crucial to have precise control over droplet characteristics, including shape, size, and generation frequency. 3 Numerous studies have demonstrated that the flow rate ratio of the two phases, the viscosity ratio, and the channel structure are the key parameters for regulating the characteristics of Newtonian droplets with simple rheological behavior. [4][5][6] Nevertheless, the mechanisms that affect the characteristics of droplets with complex rheological properties in microchannels are still relatively unknown.…”
Section: Role Of Elasticity On Polymeric Droplet Generation and Morph...mentioning
confidence: 99%
“…As a powerful platform for biochemical analysis, several classic reviews on droplet microfluidics for single-cell genomic, transcriptomic, proteomic, and metabolic analyses have been documented. Nonetheless, to the best of our knowledge, no specific review has focused on the applications of droplet microfluidics in cancer research. Herein, we first introduce the fundamental technologies of droplet microfluidics, including single/double emulsion droplet generation and active/passive droplet manipulation, aiming to help researchers easily understand the underlying mechanisms of droplet microfluidics (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…An inherent property of all microfluidic-based methods is the reduced reagent consumption due to the small volume of fluids used for operation of microfluidic devices ( Guttenplan et al, 2021a ). Compared to bulk emulsion systems, the precise control over the fluid conditions in small volumes has rendered the droplet microfluidic-based techniques suitable for producing highly monodisperse particles ( Guttenplan et al, 2021a ; Cai et al, 2021 ; Seeto et al, 2022 ), from micro-to nano-scale ( Gimondi et al, 2023 ; Nan et al, 2024 ). This also minimizes the batch-to-batch variation in terms of particle size.…”
Section: Introductionmentioning
confidence: 99%